SYSTEMATIC LITERATURE REVIEW DENGAN METODE PRISMA: DAMPAK LITERASI KEUANGAN SYARIAH TERHADAP KEPUTUSAN MENGGUNAKAN PRODUK PERBANKAN SYARIAH - Mira Chairani; Nurma Sari; Andri Soemitra; M. Shabri Abd. Majid (JIM: Jurnal Ilmiah Mahasiswa, 2025)
The purpose of this systematic literature review is to determine the methods used to analyze the role of Islamic financial literacy in the decision to use Islamic banking products, how Islamic financial literacy plays a role in the decision to use Islamic banking products, and other factors that interact with Islamic financial literacy in shaping the decision to use Islamic banking products. This study uses a Systematic Literature Review (SLR) with the PRISMA method, assisted by tools such as Watase Uake and Prisma 2020 Flow Diagram. This study is limited to journal articles indexed by Scopus and published between 2020 and 2025. Based on 137 articles reviewed through the SLR process, five articles met the criteria and were used as primary references. The research method for analyzing the dominant data is quantitative (4 articles), and there are a number of other factors that interact with Islamic financial literacy in shaping the decision to use Islamic banking products, including: level of religiosity, trust in Islamic financial institutions, skepticism, digital marketing, digital literacy, brand image and word of mouth promotion.